Prostaglandin F2α requires activation of calcium-dependent signalling to trigger inflammation in human myometrium - Riaposova, Lucia; Kim, Sung Hye; Hanyaloglu, Aylin C.; Sykes, Lynne; MacIntyre, David A.; Bennett, Phillip R.; Terzidou, Vasso (Frontiers in Endocrinology, 2023)
Introduction: Preterm birth is one of the major causes of neonatal morbidity and mortality across the world. Both term and preterm labour are preceded by inflammatory activation in uterine tissues. This includes increased leukocyte infiltration, and subsequent increase in chemokine and cytokine levels, activation of pro-inflammatory transcription factors as NF-κB and increased prostaglandin synthesis. Prostaglandin F2α (PGF2α) is one of the myometrial activators and stimulators. Methods: Here we investigated the role of PGF2α in pro-inflammatory signalling pathways in human myometrial cells isolated from term non-labouring uterine tissue. Primary myometrial cells were treated with G protein inhibitors, calcium chelators and/or PGF2α. Nuclear extracts were analysed by TranSignal cAMP/Calcium Protein/DNA Array. Whole cell protein lysates were analysed by Western blotting. mRNA levels of target genes were analysed by RT-PCR. Results: The results show that PGF2α increases inflammation in myometrial cells through increased activation of NF-κB and MAP kinases and increased expression of COX-2. PGF2α was found to activate several calcium/cAMP-dependent transcription factors, such as CREB and C/EBP-β. mRNA levels of NF-κB-regulated cytokines and chemokines were also elevated with PGF2α stimulation. We have shown that the increase in PGF2α-mediated COX-2 expression in myometrial cells requires coupling of the FP receptor to both Gαq and Gαi proteins. Additionally, PGF2α-induced calcium response was also mediated through Gαq and Gαi coupling. Discussion: In summary, our findings suggest that PGF2α-induced inflammation in myometrial cells involves activation of several transcription factors – NF-κB, MAP kinases, CREB and C/EBP-β. Our results indicate that the FP receptor signals via Gαq and Gαi coupling in myometrium. This work provides insight into PGF2α pro-inflammatory signalling in term myometrium prior to the onset of labour and suggests that PGF2α signalling pathways could be a potential target for management of preterm labour.